ENHANCING STUDENTS’ ABILITY IN SOCIOLINGUISTICS DURING THE COVID-19 PANDEMIC THROUGH ONLINE STAD–TYPE COOPERATIVE LEARNING MODEL - Raras Hafiidha Sari; Yulianah Prihatin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was initiated by the lecturers’ difficulties in presenting fun learning during the Covid-19 pandemic. This study aimed to determine the improvement of students' abilities in learning Sociolinguistics during the Covid-19 pandemic by applying STAD Type Cooperative Model implemented through the Breakoutroom Zoom Application. This application facilitated lecturers to divide students in one class into small or large groups and they could still monitor the progress of the discussion. Utilizing Student Team Achievement Division (STAD) model in the Breakoutroom Zoom application aimed to achieve a good learning process. This research was a Classroom Action Research conducted in two cycles: Cycle I and Cycle II. This research was carried out in four stages: planning, acting, observing, and reflecting. The object of this research was the sociolinguistics learning and the research subjects were the fourth semester students of Indonesian Language and Literature Education at the Faculty of Education, Hasyim Asy'ari University. There were 16 students consistinf of 4 male and 12 female students. The data were calculated quantitatively and analyzed qualitatively. Based on the results of the research, it was found that there was an increase in the Sociolinguistic learning after implementing STAD type cooperative learning model which was carried out online through the Breakoutroom Zoom application in cycle I and II. The increase was marked by an increase of the students’ score obtained in each cycle.